Effects of Geofoam Panels on Static Behavior of Cantilever Retaining Wall - Navid Hasanpouri Notash; Rouzbeh Dabiri (Advances in Civil Engineering)
Geofoam is one of the geosynthetic products that can be used in geotechnical applications. According to researches, expanded polystyrene (EPS) geofoam placed directly against a rigid retaining wall has been proposed as a strategy to reduce static loads on the wall. This study employed a finite difference analysis using a 2-D FLAC computer program by considering yielding and nonyielding states for retaining walls to explore the effectiveness of geofoam panels in improving the static performance of cantilever retaining walls. Retaining walls at heights of 3, 6, and 9 meters and geofoam panels with densities of 15, 20, and 25 (kg/m3) at three relative thicknesses of t/H = 0.05, 0.2, and 0.4 were modelled in this numerical study. In addition, the performance of the double EPS buffer system, which involves two vertical geofoam panels, in retaining walls’ stability with four panel spacing (50, 100, 150, and 200 cm) was also evaluated in this research. The results showed that use of EPS15 with density equal to 15 (kg/m3) which has the lowest density among other geofoam panels has a significant role in reduction of lateral stresses, although the performance of geofoam in nonyielding retaining walls is better than yielding retaining walls.